Biodiversity Of Eucaryotic Soil Microorganisms Tolerant To Paraquat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Margino, S., A. Budiman and E. Martani. 2004. Biodiversity of Eucaryotic Soil Microorganisms Tolerant Paraquat Biologi 3 (4): 243 - 255. This research was aimed to isolate paraquat tolerant eucaryotic microorganisms from Central Kalimantan peat soils (i.e. saphric, hemic and fibric), South Kalimantan Sulfaquept (Acid SulfateSou),andVertisolfromCentraILombok. The microorganisms were isolated using enrichment culture technique in a modified N-Free medium added with paraquat at gradually increased concentration from 10 to 40 ppm